Analysis of Investor Motivation to Buy GOTO and BUKA Shares - Mediaty Mediaty; Abdul Hamid Habbe; Andi Mujahid Darwis (Journal of Management, Economic, and Financial, 2024)
This study aims to determine the motivation of investors to buy shares in Gojek Tokopedia (GOTO) and Bukalapak (BUKA) companies. Investment motivation is a state in a person's personality that encourages the individual's desire to carry out certain activities to invest. In this study, a descriptive type of research is used which is one of the qualitative methods with the aim of the social situation to be studied. The data collection method used in this research is the Documentation technique. This research uses the literature study method, with the research objective of analyzing the motivation of investors to buy BUKA and GOTO shares. The result of this study is that although the profit generated by GOTO from 2022 to 2023 has decreased, GOTO investors continue to increase. This is due to GOTO shares which recently made it into the large cap list in the FTSE Global Asia Pacific series index (effective closing March 17, 2023) and the MSCI index (effective June 1, 2023). that is, GOTO companies have good fundamental movements and liquidity. Investor motivation in Bukalapak is quite high as evidenced by the increase in share price triggered by many investors.